2023
DOI: 10.1097/aci.0000000000000956
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of eosinophilic and neutrophilic inflammation in patients with chronic rhinosinusitis

Yutong Sima,
Xiangdong Wang,
Luo Zhang

Abstract: Purpose of review In the past year, the endotype of chronic rhinosinusitis (CRS) has been studied from a new perspective. Eosinophilic and neutrophilic inflammation are not independent processes in the pathogenesis of CRS. In this review, we will focus on recent research on mixed eosinophilic-neutrophilic inflammation in CRS and discuss the mechanism and potential treatments. Recent findings Traditionally, patients with eosinophilic CRS (ECRS) present w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…Especially potassium ion channels are widely distributed and expressed in various immune cells and are involved in antigen presentation, cell migration, phenotype transformation, and the production of inflammatory cytokines ( Pelletier and Savignac, 2018 ; Sesti et al, 2023 ; Xia et al, 2023 ). Previous studies have revealed that KCa3.1 and KV1.3 are present in T lymphocytes, and their relative expression depends on the type of T cells, including naive memory, effector memory, and central memory ( Chen et al, 2024 ; Sima et al, 2024 ). The potassium channel ERG1 and KV1.3 are involved in the maturation and differentiation of B lymphocytes ( Sima et al, 2024 ).…”
Section: The Role Of Potassium Channels In the Inflammatory Response ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Especially potassium ion channels are widely distributed and expressed in various immune cells and are involved in antigen presentation, cell migration, phenotype transformation, and the production of inflammatory cytokines ( Pelletier and Savignac, 2018 ; Sesti et al, 2023 ; Xia et al, 2023 ). Previous studies have revealed that KCa3.1 and KV1.3 are present in T lymphocytes, and their relative expression depends on the type of T cells, including naive memory, effector memory, and central memory ( Chen et al, 2024 ; Sima et al, 2024 ). The potassium channel ERG1 and KV1.3 are involved in the maturation and differentiation of B lymphocytes ( Sima et al, 2024 ).…”
Section: The Role Of Potassium Channels In the Inflammatory Response ...mentioning
confidence: 99%
“…Previous studies have revealed that KCa3.1 and KV1.3 are present in T lymphocytes, and their relative expression depends on the type of T cells, including naive memory, effector memory, and central memory ( Chen et al, 2024 ; Sima et al, 2024 ). The potassium channel ERG1 and KV1.3 are involved in the maturation and differentiation of B lymphocytes ( Sima et al, 2024 ). KV1.3, KV1.5, KCa3.1, Kir2.1/2.2, Kir6.1/6.2 and TWIK2, TREK1 can be expressed in monocytes and macrophages, regulating phagocytic function and secreting inflammatory cytokines ( Man et al, 2023 ).…”
Section: The Role Of Potassium Channels In the Inflammatory Response ...mentioning
confidence: 99%
See 2 more Smart Citations